Demographic Aspects and Investors’ Decision Making Process: A Study - Ghosh, Sutap Kumar (Journal of Asian Business Strategy, 2022)
By illustrating the demographic composition of individual investors in the DSE of Bangladesh, examining the relationship between demographic factors and investment amount, exploring the relationship between demographic factors and investors' investment periods, highlighting the relationship between demographic factors and investors' emotional state, identifying the relationship between demographic factors and the impact of internal feeling on investors’ investment decision and establishing the relationship between demographic factors and investors’ correct investment decision-making, the current study seeks to fill the knowledge gap regarding the influence of demographic aspects on investors’ decision making process. Primary data are utilized to establish and explain concepts, while secondary data are also employed to support this empirical inquiry. Here, causal-comparative and descriptive study designs have both been applied. The study sample was chosen using the judgmental sampling technique. The characteristics of each investor are described by tabulation and percentage analysis. To depict the connection between demographic factors and individual investors' investment behaviour, various hypotheses are developed. For testing the hypotheses, ANOVA and the Chi-square test are utilized. In the DSE of Bangladesh, investors' decisions about investment quantity, investment time, emotional level, internal feeling, and appropriate investment decisions are strongly correlated with respondents' gender, age, education, occupation, and income.